Mortalidade por homicídios no Brasil: diferenciais segundo a raça/cor da pele entre 2005 a 2014 - Fernandes, Alessandra Rabelo Gonçalves (2017)
Homicide mortality is a relevant public health problem, this type of violent death is a complex phenomenon of the modern world. Likewise, it also reflects the social, political and economic condition of a society, product of social disorganization due to the intense population increase and the deficiency of the supply of goods and services. Objective: To analyze spatially-temporal homicide deaths and their determinants by considering differences by race / color of skin in Brazil, from 2005 to 2014. Material and Methods: The first article is a time-series study in which it was calculated the homicide rates by sex, age and race / skin color in the Brazilian states from 2005 to 2014. The second is an ecological analytical study that had the analysis of the 27 states in Brazil, the Panel Data with Negative Binomial Regression method and fixed effects model were used. Results: In the first article, blacks accounted for 72.2% of the homicides, especially young people, both sexes, low schooling, between 20 and 29 years of age. Homicide rates have trended upward for black males and declining for white males. Women showed increasing trends regardless of race / color of the skin. The greatest variation of the annual average rates occurred in young people aged 15 to 19 years. These results were statistically significant at the 5% level. In the second article, black male overmortality was found in most Brazilian states. The areas with the highest proportion of the black male population aged 15-49 had a higher risk of death due to homicide, and even when adjusted for the other covariables present in the model did not lose strength of association and statistical significance. The HDI and unemployment rate were directly related to the homicides, while the Gini index, illiteracy rate and urbanization rate were inversely related. The results indicated a risk of death by male homicide in Brazilian states of 47.24%, whose proportion of the black population is greater than 75.0% (adjusted RR = 1.47, p = 0.01, 95% CI = 1, 18-1, 83). Conclusions: The data produced showed that the black male population aged 15 to 49 years are at higher risk of dying from homicide than white. The greater proportion of the black male population per state per se is not enough to explain homicide deaths, since homicide is a complex, multifaceted social phenomenon that still needs to be better clarified, but this is a factor that must be considered in existing public policies or in those to be implemented.